A quantum multiplier based on the quantum Fourier transform algorithm - Qian Junkai; Zhu Jialiang; Ye Bin (Dianzi Jishu Yingyong)
Multiplier is one of the basic units in many quantum algorithms. In order to implement the multiplying operations and use as few auxiliary qubits in the quantum circuit as possible, a quantum multiplier based on the quantum Fourier transform is proposed. By utilizing the quantum Fourier adder, a quantum shift circuit is designed. A quantum circuit for the multiplication of two n bit binary unsigned numbers is realized and its time complexity is O(n3). The validity of multiplying a 2 bit binary number by another 2 bit or 4 bit binary number is tested through Qiskit-an open source quantum computing toolkit provided by IBM. The experimental results show that the quantum multiplier achieves higher accuracy and lower computational complexity with less qubits. The open source code of the quantum multiplier is publicly available.